Unraveling the microstructural and optoelectronic properties of solution-processed Pr-doped SrSnO3 perovskite oxide thin films. Issue 59 (17th November 2021) - Shaili, Hamza; Salmani, Elmehdi; Beraich, Mustapha; Taibi, M'hamed; Rouchdi, Mustapha; Ez-Zahraouy, Hamid; Hassanain, Najem; Mzerd, Ahmed
Abstract : Unraveling the optical, electronic and electrical properties of high-quality nanorod morphology spray-coated Pr-doped SrSnO3 perovskite oxide thin films. Abstract : The inorganic stannous-based perovskite oxide SrSnO3 has been utilized in various optoelectronic applications. Facilitating the synthesis process and engineering its properties, however, are still considered challenging due to several aspects. This paper reports on a thorough investigation of the influence of rare-earth (praseodymium) doping on the microstructural and optoelectronic properties of pure and Pr-doped SrSnO3 perovskite oxide thin films synthesized by a two-step simple chemical solution deposition route. Structural analysis indicated the high quality of the obtained phase and the alteration generated from the insertion of impurities. Surface scanning illustrated the formation of homogenous and crack-free SrSnO3 thin films with a nanorod morphology, with an augmentation in size as the dopant ratios increased. Optical properties analysis showed an enhancement in the samples optical absorption with wide-range bandgap tuning. First-principles calculations revealed the exchange interactions between the 3d–4f states and their impact on the electronic properties of the pristine material. Hall-effect measurements revealed an immense decrement in the resistivity of the films upon increment of doping ratios, passing from 7.3 × 10 −2 Ω cm for the undoped sample to 4.8 × 10 −2 Ω cm for 7% Pr content, while a reverse trend was observed on the carrier mobility, rising from 2.5 to 7.6 cm 2 V −1 s −1 for 7% Pr content. The results emphasized the efficiency of the simple synthesis route to produce high-quality samples. The current findings will contribute to paving the way towards expanding the utilization of simple and cost-effective chemical solution deposition methods for the fast and large area growth of stannous-based perovskite oxides for optoelectronic applications.